Predicting Employee Performance by Leadership, Job Promotion, and Job Environmental in Banking Industry - Febrina, Sindy Cahya (University of Merdeka Malang, 2017)
This study aimed to analyze the effect of leadership, job promotion and job environmental simultaneously or partially had the effect on employee performance in Bank UMKM East Java Malang Branch and to analyze the variable that dominant influenced from leadership, job promotion, and job environmental employee performance. The population of this research was all 32 employees Bank UMKM branch Malang. The technique of sampling by saturated sampling, the technique through determined all population members as a sample, so the numbers of the sample in this research were 32 employees. Data collection by questioners, then the data, were analyzed by SPSS programs through multiple linear regressions analyzed. The result of the research indicated that leadership variable, job promotion and job environmental simultaneously had a significant effect on bank employee performance. Leadership variable, job promotion and job environmental partially had had a significant effect on bank employee performance and job promotion had a dominant effect on bank employee performance.DOI: https://doi.org/10.26905/jkdp.v21i4.1630Â